Policy Analysis of Women's Empowerment in Political and Government Participation - Kamila, Dewi Irabach (Kampret Journal, 2025)
This research explores the empowerment of women in political and governmental participation, analyzing the barriers they face and the policy interventions that can enhance their roles in decision-making processes. Despite significant strides in gender equality, women continue to encounter numerous obstacles, including cultural norms, economic constraints, systemic biases, and legal limitations that hinder their full participation in politics. Through a review of existing literature, the study identifies gaps in policy frameworks and assesses the effectiveness of current strategies, such as gender quotas and financial support for female candidates. The research emphasizes the importance of comprehensive policies that address these challenges, including legal reforms, economic empowerment, and educational initiatives, to create a more inclusive political environment. By highlighting the potential societal benefits of increased women’s participation, such as enhanced diversity in decision-making and greater attention to issues affecting women, the study concludes that strengthening women’s empowerment in political and governmental roles is essential for achieving sustainable development, social justice, and democratic governance. Ultimately, this study advocates for continued policy innovation to empower women, promote gender equality, and contribute to democratic and sustainable governance.